(untitled) (International Journal of Business, Economics and Management, 2021)
The study was an attempt to investigate the relationship between foreign direct investments (FDI) and the manufacturing sector contribution to GDP in Nigeria. Specific objectives included finding out the direction of causality between FDI and the growth of the manufacturing sector; and establishing the relationship between FDI net inflows and manufacturing sector contribution to GDP. To achieve the objectives, two research questions and hypotheses were formulated. Secondary data sourced from World Bank Development Indicators were used. The Granger causality model and linear regression model were employed to test the hypotheses. The empirical implementation of the model made use of macro-economic data covering the period of 30 years (1990-2019). The result showed that there is a unidirectional causality from FDI to manufacturing sector contribution to GDP. This implies that manufacturing sector contribution to GDP was not as a result of FDI inflows to Nigeria. Further findings revealed a statistically no significant linear relationship between FDI net inflows and manufacturing sector contribution to GDP in Nigeria. The implication of the study is that the little contribution made by the manufacturing sector in Nigeria is not as a result of FDI net inflows, hence there is need for government and policy makers to consider policy options that will attract FDI to the manufacturing sector.